Using modern techniques for determining the location of marketing outlet for product of the state company for vegetables oil - الشكري, عبد المنعم كاظم (Journal of Economics and Administrative Sciences, 2018)
Were arranged this study on two sections, which included first section comparison between markets proposed through the use of transport models and the use of the program QSB for less costs , dependant the optimal solution  to chose the suggested market  to locate new market that achieve lower costs in the transport of goods from factories (ALRasheed ,ALAmeen , AlMaamun ) to points of sale, but the second part has included comparison of all methods of transport (The least cost method ,Vogels method , Results Approximations method , Total method) depending on the agenda of transport, which includes the market proposed selected from the first section and choose the way in which check the solution first best suited in terms of costs and then subjecting the solution first to test a way distribution adjusted to reach the fitness in the distribution of products from sites to points of sale and end of the second topic is the comparison between the result of the program ( WIN QSB) and the result of the best solution to the transportation method which is better in terms of costs.                                      being diagnosed with the imbalance in the factories Company for vegetable oils, which leads to the flux productive products  ((Shampoo,  ALzahe , Sebon Alsail, Sebon Alger, Sebon Altiwlet, Mesahok Algesel, Alkaser) researcher suggested opening a new market for the disposal of flood productive quotient of these products after consultation with officials of the marketing department of the company and identify places proposed that in the interest of discharge flood productive happening in addition to the company's need to open markets in such places, has been to locate this market using transport models through the comparison between the markets of the proposed and deliver these products to market at less cost , and the researcher has a practical application of the use of modern methods and mathematical techniques to locate the proposed market based on data obtained from the company for the year 2011 and for the above-mentioned products.